Anxiety and Perceived Performance in Athletes and Musicians: Revisiting Martens - Núñez, Antonio; Ponseti, Francisco Xavier; Sesé, Albert; Garcia-Mas, Alexandre (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
The relationship between anxiety and performance in athletes and musicians has been studied for some time. In the present study, 132 participants from the football (n = 100) and musical (n = 32) areas participated and had an average age of 20,49 years (SD = 6,62) and an average of 11,29 (SD= 4,5) years of experience in their respective fields. The analysis have shown that there are no correlations between performance and anxiety experienced, although there are differences in the perception of anxiety between musicians and athletes, since musicians have obtained higher scores in the component of somatic anxiety.